Management of a ruptured large arteriovenous malformation: A case report - Suhadi, Andrio; Junaidi, Fachrul (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2025)
Arteriovenous malformations (AVMs) are congenital vascular disorders. In their early phase, they often go unrecognized due to their asymptomatic nature until they develop clinical symptoms such as swelling, skin discoloration, and signs of arteriovenous shunting. The high flow from the arteries directly into the veins may potentially increase the risk of vessel rupture. We reported a case of a 54-year-old male who complained of back bleeding, accompanied by pain and sores that had persisted for the previous three days. The patient had been aware of a mass since birth, progressively worsening with age. A physical examination revealed bleeding from the pulsating mass and measured approximately 17.5 cm x 15 cm x 3 cm on the back. The patient was diagnosed with ruptured AVM by Computed Tomography (CT) angiography. He was managed with endovascular coil embolization, polyvinyl alcohol particles, and skin grafts. AVMs are often asymptomatic; an ultrasound examination can be the initial diagnostic tool, while CT Angiography is considered a gold standard. AVMs are managed through embolization and surgical intervention. Regular follow-up is necessary due to the potential for recurrence.